Technology of Cultivating Plumeria Rubra Ornamental Tree under the Climatic Conditions of Uzbekistan - Misirova Surayyo Abdumutalovna; Ilxomiddinova Zulayxo Raxmonjonovna; Karimova Gulsevar Erkinjonovna (American Journal of Botany and Bioengineering, 2025)
This article analyzes the possibilities of cultivating ornamental trees of the Plumeria genus under the climatic conditions of Uzbekistan. Although the plant is naturally adapted to tropical and subtropical climates, it can be successfully cultivated in Uzbekistan with the implementation of specific agrotechnical measures. The study provides detailed information on propagation methods, care rules, irrigation and fertilization norms, and adaptation potential in different regions of the country.